Exploring Mr. Keating’s Teaching Style on Students’ Interest in Dead Poets.Society.Film - Muhammad Naufal Razan Zhafran; Eka Fitriana; Agus Saputra (Program Studi Pendidikan Bahasa Inggris, 2023)
It is important for teachers to employ an effective teaching style that can inspire and motivate the students to learn more in the class. As Saswandi (2014) said learning may occur effectively if it is motivated by a strong interest and a strong interest can be developed by the teacher's style of instruction. Nowadays, a teacher can use films containing educational information and values as a reference to develop their teaching styles, such as the Dead Poet Society film. Therefore, to help teachers identify an effective teaching style, this study analyzed Mr. Keating's teaching style which left a good impact on the students’ interests portrayed in Dead Poets Society film directed by Peter Weir. This study was a descriptive qualitative study and the primary data were gathered from the dialogues and scripts of the Dead Poet Society. For collecting the data, note-taking was utilized. The analysis and findings revealed that there were five types of teaching styles identified from the film; expert teaching style, personal model teaching style facilitator teaching style, and delegator teaching style. Whereas these teaching styles affected the students’ individual interests, situational interests, and topic interests.